Analisis Kinerja Komprehensive Sistem Pendingin Primer terhadap Efisiensi Pembangkit Listrik Tenaga Panas Bumi Tipe Flash Steam - Agus Apriyanto; Novia Utami Putri; Retno Wahyudi; Alexander Sembiring; Fauzi Ibrahim; Adam Wisnu Murti (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2025)
Abstract. Geothermal power plants rely heavily on the efficiency of their cooling systems to optimize overall energy conversion. This study investigates the performance of the primary cooling systems, namely direct contact condensers and mechanically induced flow cooling towers in Unit 3 of PT. Pertamina Geothermal Energy Tbk, Ulubelu Area, Lampung. Performance metrics are assessed using parameters such as range, approach, and effectiveness for the cooling tower, and thermal efficiency calculations for the condenser and steam turbine. Daily operational data were collected and analyzed. The results show that fluctuations in cooling tower effectiveness significantly affect condenser vacuum and turbine efficiency. The average actual cooling tower effectiveness is 70.06%, lower than the design effectiveness of 78%. The condenser shows an average thermal efficiency of 93.80%, with effectiveness variations between 83.23% to 86.44%. The turbine efficiency based on design is 87.51%, while the actual efficiency drops to the range of 81.84% to 82.48%. This decrease indicates a performance degradation of approximately 0.94% per year. This finding underlines the important role of cooling system optimization in improving the performance of geothermal power plants.